SMI Influence On Co-Branding Purchase - Andini, Ariesa Putri; Hadiprawoto, Triana Rahajeng (International Journal of Business Studies, 2024)
This study aims to determine what co-branding factors can influence consumer purchases of local fashion brand collaboration products with social media influencers. There are four co-brand factors that we want to see influence consumer purchases, namely brand coolness, product involvement, and the relationship between the brand itself and influencers. Data collection was carried out through an online survey of 206 female respondents who live in the 10 largest cities in Indonesia and know nine collaboration products of local fashion brands with influencers from various backgrounds. The collected data then will be analyzed using the structural equation partial least squares (SEM-PLS) method to measure the relationship between brand coolness, self-brand connection with influencers, product involvement, influencer expertise, perceived suitability, attitudes towards co-brands, purchase probability considering self -brand connection with fashion brands and a tendency towards novelty seeking, Based on the research concluded that brand coolness has positive influence but no significant effect on perceived fit. Self-brand connection with influencers is unable to moderate the relationship between brand coolness with perceived fit, product involvement has a negative effect but not a significant effect on perceived fit. This study shows that there is a relationship between SMI expertise with perceived fit. Meanwhile, SMI expertise has positive effect but not significant on attitude towards co-brand and expertise has a negative and insignificant effect on purchase probability, perceived fit has positive and significant effect on attitude towards co-brand, noted that attitude towards co-brand positively and significantly has an effect on purchase probability.